A physical explanation for the development of redox microzones in hyporheic flow. Issue 11 (2nd June 2015) - Briggs, Martin A.; Day‐Lewis, Frederick D.; Zarnetske, Jay P.; Harvey, Judson W.
Abstract Recent observations reveal a paradox of anaerobic respiration occurring in seemingly oxic‐saturated sediments. Here we demonstrate a residence time‐based explanation for this paradox. Specifically, we show how microzones favorable to anaerobic respiration processes (e.g., denitrification, metal reduction, and methanogenesis) can develop in the embedded less mobile porosity of bulk‐oxic hyporheic zones. Anoxic microzones develop when transport time from the streambed to the pore center exceeds a characteristic uptake time of oxygen. A two‐dimensional pore‐network model was used to quantify how anoxic microzones develop across a range of hyporheic flow and oxygen uptake conditions. Two types of microzones develop: flow invariant and flow dependent. The former is stable across variable hydrologic conditions, whereas the formation and extent of the latter are sensitive to flow rate and orientation. Therefore, pore‐scale residence time heterogeneity, which can now be evaluated in situ, offers a simple explanation for anaerobic signals occurring in oxic pore waters.